2015
DOI: 10.1093/brain/awv267
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid neurogranin: relation to cognition and neurodegeneration in Alzheimer’s disease

Abstract: Synaptic dysfunction is linked to cognitive symptoms in Alzheimer's disease. Thus, measurement of synapse proteins in cerebrospinal fluid may be useful biomarkers to monitor synaptic degeneration. Cerebrospinal fluid levels of the postsynaptic protein neurogranin are increased in Alzheimer's disease, including in the predementia stage of the disease. Here, we tested the performance of cerebrospinal fluid neurogranin to predict cognitive decline and brain injury in the Alzheimer's Disease Neuroimaging Initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
243
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 235 publications
(262 citation statements)
references
References 36 publications
17
243
2
Order By: Relevance
“…The elevated Ng in AD may not be specific to hippocampal atrophy and may represent more widespread global degeneration, perhaps in AD related areas including the parietal cortex. Our results may be a consequence of small sample size and the cross‐sectional nature of this study, noting that previous studies have reported no association between CSF Ng and hippocampal volumes in a similar cross‐sectional analysis6; it may be that rates of atrophy derived from longitudinal assessments would better reflect the rate of synaptic loss. Finally, the CSF levels of neuronal and synaptic proteins such as tau and Ng are believed to reflect the state (or intensity) of the degenerative process, while MRI measurements of cortical volumes reflect the stage of degeneration,29 and thus these measures may not be expected to correlate well.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The elevated Ng in AD may not be specific to hippocampal atrophy and may represent more widespread global degeneration, perhaps in AD related areas including the parietal cortex. Our results may be a consequence of small sample size and the cross‐sectional nature of this study, noting that previous studies have reported no association between CSF Ng and hippocampal volumes in a similar cross‐sectional analysis6; it may be that rates of atrophy derived from longitudinal assessments would better reflect the rate of synaptic loss. Finally, the CSF levels of neuronal and synaptic proteins such as tau and Ng are believed to reflect the state (or intensity) of the degenerative process, while MRI measurements of cortical volumes reflect the stage of degeneration,29 and thus these measures may not be expected to correlate well.…”
Section: Discussionmentioning
confidence: 63%
“…It is a postsynaptic protein that is mainly expressed in the cortex and hippocampus, where it is concentrated in dendritic spines, and has a major role in regulating LTP and learning. Cerebrospinal (CSF) Ng is elevated in patients fulfilling clinical criteria for AD compared to mild cognitive impairment (MCI) patients as well as controls, a finding that has been replicated using different assays and across clinical sites 4, 5, 6, 7. Importantly, it has not yet been determined if it is also elevated in atypical forms of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the cross-sectional nature of the study, it was not possible to differentiate stable-MCI subjects from those progressing and converting into dementia. Further studies are needed to confirm the potential value of neurogranin in predicting conversion from MCI to AD [17,18]. Extensive psychometric data were not available in our study, thus preventing the study of CSF neurogranin concentrations in relation to different cognitive dimensions.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with healthy controls (HC), cerebrospinal fluid (CSF) neurogranin concentrations are increased in patients with AD [13][14][15] and subjects with mild cognitive impairment (MCI) as well as MCI progressors and converters to AD (MCI-AD) [13,16]. Moreover, neurogranin predicts progression from MCI to AD dementia [13,17,18] and rate of cognitive decline [13], and correlates longitudinally with rates of hippocampal atrophy [18,19] as well as with reduced regional cortical glucose metabolism assessed by 18 F-Fluorodeoxyglucosepositron emission tomography ( 18 F-FDG-PET) [18]. Very recently, CSF profiling of the human brain enriched proteome has confirmed a significant association between increased neurogranin concentrations and AD [20].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Furthermore, Ng can predict conversion from mild cognitive impairment to AD, as well as predict faster cognitive decline and hippocampal atrophy rates in amyloid-positive patients with prodromal AD. 15,18 Using a sensitive sandwich immunoassay with electrochemiluminescence detection to investigate the CSF from well-characterized patients with AD and a range of other neurodegenerative disorders associated with synapse dysfunction, we aimed to explore to what extent Ng increase is specific to AD.…”
mentioning
confidence: 99%